PPARβ/δ ligands regulate the expression of immune response mediators in the porcine endometrium – An in vitro study - Kunicka, Zuzanna; Kurzyńska, Aleksandra; Szydłowska, Anna; Kaczyńska, Beata; Bogacka, Iwona (Theriogenology, 2019)
The peroxisome proliferator-activated receptor (PPAR) β/δ belongs to a group of nuclear receptors that act as transcription factors. PPAR β/δ plays a significant role in the regulation of female reproductive processes. It has been demonstrated that PPARβ/δ is expressed in mouse, rat and porcine endometrium during the estrous cycle and pregnancy. The current study aimed to investigate the effect of selected PPARβ/δ ligands on the expression of nuclear factor kappa (NF-κB) and selected cytokines – interleukin (IL)-1β, IL-6, IL-8, IL-4, IL-10, leukemia inhibitory factor (LIF), in the porcine endometrium on days 10–12 and 14–16 of the estrous cycle (mid- and late-luteal phases corresponding to the full activity and luteolysis of the corpus luteum, respectively) and pregnancy (maternal recognition of pregnancy and beginning of implantation, respectively). Endometrial slices were incubated in vitro in the presence of PPARβ/δ agonist L-165,041 (1 or 10 μM) or antagonist GW9662 (10 μM). The expression of mRNA and protein of the immune response mediator in the tissues was determined by real-time PCR and Western Blot. In general, the PPARβ/δ agonist inhibited endometrial NF-κB mRNA expression during all analyzed reproductive stages, but it did not change protein expression. In turn, the PPARβ/δ antagonist increased NF-κB protein levels on days 10–12 of the estrous cycle or pregnancy. The presence of the PPARβ/δ agonist stimulated mRNA expression of LIF, IL-1β and IL-8 and decreased the expression of IL-6. The presence of PPARβ/δ ligands had a varied effect on protein expression in different stages on the analyzed period. The obtained results indicate that PPARβ/δ regulates the expression of endometrial NF-κB and selected cytokines in pigs. The effects of PPARβ/δ ligands on immune response mediators varied subject to the reproductive status of females and could be associated with differences in endometrial receptivity. •PPARβ/δ ligands affected NF-κB and cytokine synthesis in the porcine endometrium.•The ligands were effective during the estrous cycle and early pregnancy.•PPARβ/δ ligands inhibited NF-κB expression in the porcine endometrium.•PPARβ/δ enhanced anti-inflammatory cytokines expression in the porcine endometrium.•Diverse receptivity of the tissue is associated with the reproductive stage of pigs.